A Literary and Linguistic Approach in the Tafsīr Methodology of "Aisyah Abd al-Rahman (Bint al-Shāṭi)" - Wiwik Prasetiyo Ningsih; Umi Sumbulah; Mohammad Zainal Hamdy (Al-Irfan : Journal of Arabic Literature and Islamic Studies, 2023)
Al-Qur'an is the Arabic language holy book that contains the highest literature. Then the interpretation of the Qur'an will be more objective if it is done with a literary approach, not a scientific or other approach. Because of the characteristics of the Qur'an itself which is the highest literature, it would be more appropriate to approach it with a language literature approach. This paper aims to describe the language literature approach that’s contained in Bintu Syathi's interpretation methodology. This research is a qualitative research with a type of literature review. The results of this study are that the language literature approach contained in Bintu Syathi' thematic interpretation methodology is never separated from extrinsic criticism and intrinsic criticism. He uses extrinsic criticism at the stage of understanding the what arroud of the Qur'an. Meanwhile, he used intrinsic criticism at the stage of understanding the mafi Al-Qur'an or what is in the Qur’an when interpreting the Al-Qur'an